Genetic structure and connectivity of the critically endangered deep-sea octocoral Isidella elongata: implications for marine biodiversity conservation in the Mediterranean Sea - LAURIA, VALENTINA; GARGANO, FRANCESCO; ARCULEO, MARCO; BONO, GIOACCHINO; FIORENTINO, FABIO; FLOT, JEAN-FRANÇOIS; COLLARD, OLIVIER; FOLLESA, MARIA CRISTINA; GAROFALO, GERMANA; GEORGES, VINCENT; MAIORANO, PORZIA; MASSI, DANIELA; et al. (Mediterranean Marine Science, 2025)
The protection of the Vulnerable Marine Ecosystem identified by the presence of the critically endangered bamboo coral Isidella elongata has been recognized as an urgent task. Although some research has focused on the spatial distribution of this species, there is no information available on its connectivity and genetic structure. This is the first study to examine the genetic diversity pattern and inter-population connectivity of I. elongata at the Mediterranean scale. The DNA-based approach for assessing the genetic diversity of 33 I. elongata samples collected in six different areas involved two mitochondrial markers (COI and MutS) and one nuclear marker (ITS2). Molecular results confirmed that all samples belonged to I. elongata and showed a scarce level of intra- and inter-population mtDNA differentiation, whereas nuDNA data revealed genetic structuring. Furthermore, a Lagrangian model (forward-in-time simulations) was used to investigate the species larval connectivity under different sea current conditions. Our results suggest the presence of persistent pathways, supporting the self-sustaining nature of the populations, especially in the central Mediterranean Sea. This study identifies the main corridors of connectivity for I. elongata in the Mediterranean Sea, highlighting the importance of including such information in the implementation of fishery management measures.